Rywalizacja na wizerunki w wyborach prezydenckich w Polsce - Ilciów, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author presents the evolution and specificity of presidential elections in Poland in the context of broader political processes taking place since the early 1990s. Particular emphasis is placed on the analysis of changes in electoral law, election campaign mechanisms, the impact of media and technology on shaping the political message and the emotional impact on voters. The presidential election campaign simultaneously promotes the party and mobilizes its members and voters. The analysis of selected campaigns shows the complexity of strategies, tools and social reactions, as well as the impact of the presidential election on subsequent changes in the balance of political power.
Keywords: rywalizacja; wizerunek; kampania wyborcza; wybory prezydenckie; competition; image; election campaign; presidential elections